Quality of care, loss to follow-up and mortality among paediatric and adolescent HIV patients on antiretroviral therapy in Abuja, Nigeria: a 15-year retrospective review - Okechukwu, Adaora A.; Okechukwu, Orji A.; Lamda, Nansah R. (International Journal of Research in Medical Sciences, 2022)
Background: Loss to follow up, and mortality still remains very high among HIV positive children and adolescents in many under privileged settings, in spite of massive scale up of anti-retroviral treatment. We assessed the quality of care using 7-point indicators, loss to follow up, and mortality among HIV positive children and adolescents in our health institution. Method: A 15-year (2006 to 2020) retrospective review was conducted among HIV positive children who assessed care in paediatric out-patient special treatment clinic of our tertiary health institution in Nigeria for above objective. Results: Of the 563 subjects initiated on antiretroviral therapy, 349 (62.0%) still remained on treatment. There were 285 (50.6%) males, highest enrollment 280 (49.7%) was at 2006-2010, most 192 (34.1%) were 0-24 months of age, 244 (43.3%) were under-weight, and 176 (31.3%) had severe immune suppression at enrollment. Sixty-eight (12.1%) were lost to follow-up, mortality was 14 (2.5%), 103 (18.3.1%), and 25 (4.4%) were transferred to adult clinic, and to other centers. While over 85% had a high-quality indicator score of 458 (81.4%), with significant difference between the male and female (x2=8.56, p=0.003,), only 231 (66.2%) had adequate viral suppression of <20 cpoies/ml at the end the review period. There was significant association between quality indicator score and loss to follow up, OR=0.033 (0.02-0.06), p>0.001 with multivariate analysis. Conclusions: Though the study recorded high quality score services to HIV positive children and adolescents in our center, loss to follow-up, and mortality was however high. More is needed to be done to improve the viral load suppression among our clients.